Pengujian Keputusan Fiktif Positif Di Pengadilan Tata Usaha Negara - Desy Wulandari (Universitas Islam Indonesia, 2020)
Article 53 of Law Number 30 of 2014 on Government Administration (Law 30/2014) does not provide an explanation of the criteria for positive fictitious decisions/actions of Government Agencies and/or Officials, but rather authorizing the State Administrative Court to review the reports on positive fictitious decisions/actions. As a form of expansion of the object of disputes in the State Administrative Court, positive fictitious decisions/actions require in-depth study considering there are obstacles in their implementation as well as the review at the State Administrative Court. This writing intends to determine the criteria for positive fictitious action of Government Agencies and/or Officials and to find out how to test positive fictitious decisions / actions by the State Administrative Court. This is a normative legal research, in which the results indicate, first, the criteria for positive fictitious decisions/actions can be identified by exploring the principal elements in Law 30/2014 and in the Supreme Court Regulation Number 8 of 2017. Second, the examination of positive fictitious decisions/actions is by using applicable laws and regulations and general principles of good governance.